Pertanggungjawaban Pidana Bagi Pelaku Penyertaan (Deelneming) Yang Tidak Memiliki Kualitas Pribadi dalam Tindak Pidana Korupsi - Abdul Muflihun; Ufran Ufran (Faculty of Social Science, Universitas Negeri Padang, 2020)
This study was to determine the criminal liability for the actors of participants who did not have personal qualities in corruption and to find out the legal considerations of judges in court decisions against the actors of participants who did not have personal qualities in criminal acts of corruption. The research method used was a normative legal research method. Participants who had no personal quality could be held crimanally accountable, the basis of the consideration was first because there was no clear legal basis and secondly supported by the opinions of several experts in criminal law. The relationship of each participant was not separate from one another but becomes a unity, meaning that one actors could also determine the other actors accountability. A clarity was needed on whether or not perpetrators who did not have personal qualities were accountable for their actions, namely by making legal decisions that remain jurisprudential or making new articles formulated in the upcoming law on corruption eradication.